Meningkatkan Kemampuan Bahasa Inggris Dengan Penggunaan Lagu di Lingkungan V Kelurahan Sei Putih Barat – Medan Petisah, Sumatera Utara - Kresna Ningsih Manik; Dolli Rotua Sinaga (Fakultas Teknik Universitas Cenderawasih, 2022)
This activity emerged from the inspiration and desire of the writers to improve the English language skills of students in the neighborhood where the writers live, namely neighborhood V, Sei Putih Barat sub-district, Medan Petisah District, North Sumatra Province, who basically still have difficulties in understanding the language. English, especially in the Vocabulary aspect, is why the authors held this activity with the hope that students will have good knowledge after participating in this activity. Community Service (PKM) is an integral aspect of community progress and sustainable development. By actively engaging in community-based initiatives, individuals, organizations and institutions contribute to addressing social problems, building trust and fostering social cohesion. This activity involved around 20 students ranging in age from 8 - 12 years. This activity will be carried out for around 3 days, namely 17 – 19 November 2022 with a duration of 90 minutes/session. The song titles used are (1) Hokey Pokey, (2) 10 little Indians, (3) Head shoulders knees and toes, (4) Bingo, (5) Good Morning, (6) ABC, (7) Old Mc Donald had a farm, (8) London bridge is falling down, (9) There was an old lady who swallowed a fly, (10) There was an old lady who swallowed a fly, (11) 10 green bottles, (12) If you 're happy and you know it. After carrying out this activity, the students showed an increase in vocabulary, it was seen that they were able to fill in the blanks to complete the song after listening to it several times.